ISLAMIC EDUCATION IN A MINORITY SETTING - Muhammad Fahmi; M Ridlwan Nasir; Masdar Hilmy (IAIN Tulungagung, 2020)
This study documents how multicultural education is constructed and implemented in a local pesantren in Tabanan, Bali, Indonesia, namely PBBI (Pesantren Bali Bina Insani). It demonstrates that the multicultural education in this pesantren is based upon the reality of religious, cultural, ethnic, group, and gender diversity that exists surrounding the pesantren. Teaching and administrative staff of this pesantren consist of Muslims and Hindus. Students come from the different socio-cultural backgrounds. Inclusive and tolerance values are incorporated into the curriculum of the pesantren. Multicultural education in this pesantren has become a strategic instrument for adaptation to the Hindu environment where it is located. The pesantren teaches students how to implement Islamic teaching on pluralism and inclusivism in their daily activities.